Role of Diethylstilbestrol on Growth of Green Chromide, Etroplus suratensis - V., Jayaprakas; C., Sambhu (Fishery Technology, 2025)
Green chromide was cultured by feeding diets supplemented with five levels (1, 2, 3, 4 and 5 ppm) of diethylstilbestrol for 120 days in a brackish water pond and its growth performance was evaluated. Diethylstilbestrol at 2 ppm level produced significantly (p<0.01) superior growth over the control. Feed consumption, conversion efficiency and nutrient digestibility were improved due to the supplementation of hormone in the diet. Gonadosomatic index was high in the fishes fed maximum dosage of diethylstilbestrol. The RNA/DNA ratio and protein contents in the muscle increased with the high growth rate. In green chromide, diethylstilbestrol stimulated protein synthesis and promoted growth through enhanced digestive enzymes activity and improved nutrient digestibility.